Analysis of the positional relationship between the left brachiocephalic vein and its surrounding vessels via computed tomography scan: A retrospective study. (July 2020) - Mitsuoka, Hiroki; Arima, Takahiro; Ohmichi, Yusuke; Naito, Munekazu; Hagihara, Makiyo; Nakano, Takashi; Ishibashi, Hiroyuki
Objectives: This study aimed to clarify the positional relationship between the left brachiocephalic vein and its surrounding vessels and to analyse the association between this positional relationship and ageing. Method: Chest contrast-enhanced computed tomography was performed for 100 adults. The contact number between left brachiocephalic vein and surrounding vessels (aorta, brachiocephalic artery, left common carotid artery and left subclavian artery) was determined. The correlations of ageing with the cross-sectional areas of left brachiocephalic vein crossing brachiocephalic artery and left common carotid artery and peripheral end of left brachiocephalic vein were analysed. Results: LBV was in contact with aorta in 19, brachiocephalic artery in 97, left common carotid artery in 90 and left subclavian artery in 21 patients. There were significant negative correlations of ageing with the cross-sectional areas of left brachiocephalic vein crossing brachiocephalic artery and left common carotid artery and peripheral end of left brachiocephalic vein. Conclusions: Brachiocephalic artery and left common carotid artery have easy contact with left brachiocephalic vein. There was a negative relationship between the cross-sectional area of left brachiocephalic vein and age.